PENGEMBANGAN KOMPETENSI GURU SEKOLAH DASAR MELALUI PENELITIAN TINDAKAN KELAS - Meilina Bustari (Dinamika Pendidikan, 2009)
A good education needs professional teachers. Professional teachers needs professional development programs. A professional development program that can be done by teachers is doing Classroom Action Research. Classroom action research is a practical research by teachers in class for  improving instructional  quality through planning, implementing, observing. and reflecting activities. All activities in classroom  action  research  will  improve  teacher  competencies. Successful implementation of classroom action research needs support and facilitation  from school staffs especially the principal.   Keywords:  Improve teachercmpetencies, classroom action research.